Real‐world cost estimates of initiating emicizumab in US patients with haemophilia A. Issue 4 (29th May 2021) - Samelson‐Jones, Benjamin J.; Guelcher, Christine; Kuhn, Jan; Butler, Regina; Massey, Gita; Guerrera, Michael F.; Raffini, Leslie
Abstract: Introduction: Emicizumab is the first approved non‐factor therapy for haemophilia A. It provides superior prophylactic bleeding control compared to other products in both patients with and patients without inhibitors. However, there is no real‐world data about the monetary consequences of starting emicizumab. Aim: To examine the estimated costs of starting emicizumab in a cohort of real‐world haemophilia A patients with and without inhibitors. Methods: The cost of haemostatic therapy for 6 months before and after initiating emicizumab for participants in a multicentre observational study was calculated based on the type of product and dosing that was used for prophylaxis and treating breakthrough bleeds, the number of treated bleeds and the participant weight. Results: Ninety‐two patients were included, 18 with an active inhibitor. The median age was 8.7 years. The median total cost for all patients decreased from 176, 720 to 128, 099 ( p = .04) after initiating emicizumab, largely because of decrease in the total cost of high‐cost outliers. The cost of prophylaxis and the total cost of bleeds also significantly decreased after starting emicizumab, both for patient with and patients without inhibitors. Conclusions: Starting or switching to prophylaxis with emicizumab results in decreased costs for the treatment of patients with haemophilia A. This real‐world data could inform on payer decisions as well as future cost‐effective analysis.